High rates of cervical cancer among HIV-infected women at a referral hospital in Malawi. (August 2016) - Kohler, Racquel E; Tang, Jennifer; Gopal, Satish; Chinula, Lameck; Hosseinipour, Mina C; Liomba, N George; Chiudzu, Grace
Cervical cancer is the most common cancer among women in Malawi. National guidelines recommend screening women aged 30–45 years every five years; however, no specific recommendations exist for women with HIV. We aimed to assess the frequency of high-grade dysplasia (CIN 2 or CIN3) and cervical cancer among women in central Malawi and to examine associations with CIN2+ (CIN2/3 or cancer). We extracted cervical Pap smear, biopsy, loop electrosurgical excision procedure and uterine specimen reports from a hospital pathology database from November 2012 to November 2013. We used logistic regression to estimate associations with CIN2+. We reviewed specimens from 824 women; we excluded 194 with unknown HIV status, leaving 630 in the analytic sample. Twelve percent had high-grade dysplasia and 109 women (17%) had cancer. Twenty-five percent of high-grade dysplasia cases and 35% of cancers occurred among women outside recommended screening ages. The odds of having CIN2+ were 6.55 times (95% CI 4.44-9.67) greater for HIV+ women. High-grade dysplasia and cervical cancer are very common among Malawian women, especially HIV+ women. HIV infection was strongly associated with CIN2+. Expanding screening to women not covered by current guidelines could avert a substantial proportion of cervical cancer cases in Malawi.